2019
DOI: 10.1177/1535370219842149
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan in a rat model of testicular toxicity: New insight on its protective mechanism

Abstract: Cisplatin (CDDP) is widely used as an effective chemotherapy; nevertheless, its use is associated with male reproductive system damage. Candesartan (Cand) is an angiotensin II receptor blocker which showed a protective effect against CDDP-induced testicular toxicity. This study was implemented to investigate further novel molecular protective effect of Cand. Animals were divided into four groups and treated for 10 days as: Group I (Normal control): received saline, Group II (Cand control): treated with Cand (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(115 reference statements)
2
3
0
Order By: Relevance
“…At the same time, it decreased the expression of the pro-apoptotic Bax and Cyt-C. These findings are consistent with previous studies that found candesartan could attenuate apoptosis via modulating apoptotic and anti-apoptotic proteins [ 49 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, it decreased the expression of the pro-apoptotic Bax and Cyt-C. These findings are consistent with previous studies that found candesartan could attenuate apoptosis via modulating apoptotic and anti-apoptotic proteins [ 49 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, candesartan administration remarkably restored the antioxidant balance. Sherif and Sarhan [ 49 ] reported that candesartan antagonizes the oxidative stress damage elicited by Ang II in cisplatin-induced testicular damage. Furthermore, we found that Cd toxicity caused a marked decrease in Nrf2 levels in hepatic and renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our results illustrated that cisplatin greatly reduced body weight. These results were consistent with the reports made (30,31). As we know, a lot of chemotherapy drugs such as cisplatin can in uence the digestive system like nausea, vomiting and diarrhea.…”
Section: Discussionsupporting
confidence: 93%
“…These results weren't consistent with the results of the work of Azarbarz et al (33). Decreased TSI occurs following a decrease in testicular mass that can occur due to suppression of spermatogenic function in the testes and atrophy of seminiferous tubules by cisplatin administration (30,31,34). This improvement in TSI and body weight in different SNA-treated groups can be attributed to the results of studies on satiety hormones such as leptin, which can increase appetite and overeating (35).…”
Section: Discussionmentioning
confidence: 76%
“…A total of 300 spermatozoa were examined on each slide (3000 cells in each group), and the head, tail, and total abnormality rates of spermatozoa were expressed as percentages as previously explained. [ 31 ]…”
Section: Methodsmentioning
confidence: 99%